PENERAPAN DIVERSI OLEH HAKIM DALAM MENDAMAIKAN ANAK PELAKU DAN KORBAN TINDAK PIDANA PENCURIAN (Studi di Pengadilan Negeri Medan) - Roland Tampubolon; Syafruddin Kalo; Muhammad Hamdan; Marlina Marlina (Universitas Sumatera Utara, 2018)
ABSTRACT Medan District Court has dealt with 165 juvenile criminal cases in the last two years, 2015 and 2016, and 91 of the cases are dealt with theft done by children. The data from Medan District Court show that theft by minors is the most frequently found cases handled by the judge in Medan District Court in the last two years; more than half of all cases, which are mostly pronounced a sentence by the judge. That there are many cases of diversion failure in Medan District Court indicates that there is diversion failure in police or judiciary level. This condition has encouraged the author to bring up the title “The Implementation Of Diversion By Judge To Juvenile Thefts And Victims Of Theft Crime (A Study At Medan District Court).” Keywords: Theft Crime, Diversion